De-radicalization in the Implementation of Islamic Education Curriculum in SMA Masamba South Sulawesi - Rustan, Edhy; Hanifah, Nurul; Kanro, Bulu’ (Dinamika Ilmu: Jurnal Pendidikan, 2018)
The emergence of radicalism problem has threatened disintegration of nation. Therefore, it needs a big role of education especially Islam religious education in preventing the understanding of radical religious teachings, maintaining the character of loving peace and nationalism values. Thus, this research is important to be conducted. This research aims to elaborate de-radicalization of Islamic teachings in Senior High School. This research used descriptive qualitative approach. Research data was obtained from the implementation of curriculum 2013 by senior high school teachers of Islamic religious education in Masamba, South Sulawesi. Data collection was done through direct observation, in-depth interview, and documentation. Data validity was checked through source triangulation and methods. The analysis was done by collecting, presenting, reducing, and drawing conclusion. The results of research were shown that de-radicalization in Islamic education faced several obstacles in achieving assessment standard. Nevertheless, Islamic education in curriculum 2013 can foster students’ character of religious, tolerant, democratic, and peace-love. As an effort of preventing, de-radicalization was done early through Islamic education. The practice of de-radicalization was carried out by teachers in a form of introducing and implementing religious values, tolerance, and nationalism in learning process by integrated with syllabus, teaching materials, and lesson plan.